SINOM FRESH HERBAL DRINK MINUMAN SEHAT BAGI MASYARAKAT TERDAMPAK PANDEMIC COVID 19 - windasari windasari; Nunuk Hariyati; mohammad syahidul haq; mudjito mudjito (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2021)
The number of patients who died being infected the Covid-19 virus increases significantly. The data shows that currently in Ponorogo there are: 19739 ODR; 198 OTG; 424 ODP; and 24 CONFIRMED. One of the efforts to prevent spread of the Covid-19 virus is by maintaining people health or maintaining body immunity. Sinom is a traditional herbal drink that has been widely known and used by the community to cure minor ailments, prevent disease, and maintain endurance and body health. This Community Service Program (PKM) is to help the government in efforts to prevent spread of the Covid-19 Virus by improving public health through consumption of Sinom Fresh Herbal Drink which is distributed to people affected by Covid-19 in the Ponorogo Region. The method used in this program is through sinom distribution, independent empowerment of sinom production through video tutorials and empowerment of youth organizations in the sinom distribution process. The PKM outputs include: (1) 200 bottles (@ 350ml) Sinom Herbal Drink and (2) Distribution of Sinom Herbal Drink, Video Tutorials and PIRT Handbooks to people affected Covid-19 by empowering Karang Taruna Desa Poko, Jambon District, Ponorogo region